1994
DOI: 10.1288/00005537-199403000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of facial canal dehiscence and of persistent stapedial artery in the human middle ear: A report of 1000 temporal bones

Abstract: A total of 1000 temporal bones were used to study the prevalence of facial canal dehiscence and of persistent stapedial artery in detail. Of the temporal bones studied, 560 (56%) contained at least one facial canal dehiscence. There was a 76.3% prevalence of bilaterality of this canal wall gap. The most common site of dehiscence was the oval window area. The concept of microdehiscence of the facial canal is introduced. One third of the temporal bones observed had a microdehiscence of the facial canal, usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(87 citation statements)
references
References 28 publications
2
74
0
11
Order By: Relevance
“…In cadaver and temporal bone studies, dehiscence rates of between 10 and 74 per cent have been reported. [16][17][18][19] Computed tomography detection of facial canal dehiscence has a sensitivity of 66-66.6 per cent and a specificity of 84-98 per cent. 20,21 Hence, it could be hypothesised that our second and third cases did actually have microdehiscences of the fallopian canal on the side of the development of their palsy, which were not obvious on their CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…In cadaver and temporal bone studies, dehiscence rates of between 10 and 74 per cent have been reported. [16][17][18][19] Computed tomography detection of facial canal dehiscence has a sensitivity of 66-66.6 per cent and a specificity of 84-98 per cent. 20,21 Hence, it could be hypothesised that our second and third cases did actually have microdehiscences of the fallopian canal on the side of the development of their palsy, which were not obvious on their CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…5 Moreano et al examined 1000 temporal bones and found unilateral dehiscence of facial canal in 56% and bilateral dehiscence in 76.3% of temporal bones. 6 Temporal bone specimen of newborns revealed much higher incidence of multiple dehiscence along the facial canal.…”
Section: Discussionmentioning
confidence: 97%
“…Chemical cauterization of a posterior perforation renders the facial nerve at a high risk of burn from the dripping silver nitrate solution because the tympanic segment dehiscence can be present in up to 56% of ears [7,8] . In addition, the trickling of silver nitrate into the retrotympanum may lead to its absorption through the round window membrane into the inner ear causing its damage.…”
Section: Discussionmentioning
confidence: 99%